A critical analysis of the small business credit gap and alternative lenders' strategies to effectively serve the small business sector - Rosencrance, Austin (2017)
Credit, in the form of a bank loan, is a lifeline for small businesses in the United States. When the human heart stops beating or becomes debilitated, ultra measures are taken to repair it. Credit, like the heart, keeps small businesses functioning, allowing them to provide essential services and goods to the public. Following the financial crisis in 2007-2008, small businesses lost access or found it extremely hard to receive external financing, particularly from a bank. Actions taken over the pursuing years, that were intended to prevent another recession, may have inadvertently affected banks’ ability to give credit to small businesses. Furthermore, this created a market for small business financing, and now a group of technology firms, referred too as alternative lenders, appear to be competing for this niche market.